Physical Quality of Culled Duck Meatball Substituted with Edamame Flour Filler - Prayitno, Agus Hadi; Wibisono, Gilang Setyo (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This study aimed to determine the effect of edamame flour filler substitution on the physical quality of culled duck meatballs. The research material consisted of culled duck meat, tapioca flour, edamame flour, albumen, garlic, onion, salt, pepper, monosodium glutamate, sodium tripolyphosphate, and ice. The edamame flour filler substitution treatments were P0 (0%), P1 (5%), P2 (10%), P4 (15%), and P5 (20%) from total filler. Each treatment consisted of five replications. The parameters which tested were pH value, water holding capacity, cooking loss, and chewiness. The data on physical quality results were analyzed by analysis of variance using completely randomized design and if there was significantly (P<0.01), then that tests further by the Duncan's New Multiple Range Test. The results showed that the substitution of edamame flour filler to the level of 20% had a highly significant effect (P<0.01) on pH value, water holding capacity, cooking loss, and tenderness of culled duck meatballs. The edamame flour filler substitution at the level of 20% can increase the pH value, water holding capacity, and cooking loss, but decrease chewiness of culled duck meatballs.